Teacher's Ability To Conduct Deep Assessmentcitizenship Education Learning (Pkn) At Satria Mandiri Private Junior High School, Bandar Tongah. - Nasution, Ade Mey Lisca; Gultom, Sariaman; Saragih, Krissi Wahyuni; Napitu, Ulung; Corry, Corry (JUPE : Jurnal Pendidikan Mandala, 2023)
Evaluation is an important component in the education system. Evaluation of achievement is separate from the teaching and learning process; In addition, it is very important in the education and teaching system in educational institutions. Improvement and development of education can be identified by the evaluation results. Thus, through evaluation teachers will be able to identify how successful their teaching and learning process is planning and discover the level of program efficiency. Qualitative methods are used in this research. Observation, interview, and documentation of data collection techniques used. Data analysis techniques are data reduction, presentation, and drawing conclusions. The results of this research show that the teacher's ability to teach Civic Education evaluates the learning process in SMP Swasta Satria Mandiri, the teacher has carried out eight evaluation criteria in the teaching and learning process, namely: consistency between the teaching and learning process and the curriculum, implementation by the teacher, implementation by students, student motivation, liveliness, interaction, teacher's ability to teach, student achievement quality; However, the weakness caused by the teacher's lack of ability in planning and evaluating implementation in SMP Swasta  Satria Mandiri. The teacher's ability To Carry Out The Final Evaluation In Learning Citizenship Education at The Satria Mandiri Private Vocational School is quite good. Although in general the evaluation has been carried out well, some weaknesses were found. Suggestions for this research are that Civics teachers in SMP Swasta  Satria Mandiri need improvement in making good lesson plans, and teachers should record student improvements in the learning process in organized notes such as Discussion Assessment sheets, affective Assessment sheets for student objectivity scores.